Report on Employer-Employee Relations in the Public Service of Canada - Finkelman, Jacob (Relations industrielles / Industrial Relations, 1974)
In this article, the author explains the rationale behina the Finkelman report which contains many proposals for legislative change in the Public Service Staff Relations Act„ Some of the key recommendations are discussed but substantial consideration is also given to the constraints the committee had to deal with.